Algorithms for Thermal Control Systems with Artificial Intelligence Based on Fuzzy Logic - Nigmatov Azizjon Makhkamovich; Yunusova Sayyora Toshkenboevna (Zien Journals, 2024)
Drying cotton and cotton raw materials is an important step in their production, requiring significant energy consumption. This article discusses methods for improving energy efficiency in cotton drying. In particular, schemes and formulas are presented for optimizing the drying process using modern technologies and energy saving methods
Keywords: Electricity; drying; energy saving; efficiency